Hypotension: an unusual presentation of vitamin B12 deficiency, with complete recovery following cyanocobalamin therapy. Issue 12 (5th December 2019) - Yousaf, Zohaib; Razok, Almurtada; Elzouki, Abdel-Naser; Sabobeh, Taher
Abstract : Vitamin B12 deficiency and its sequelae are well described and reported, especially in vegetarians. However, its association with haemodynamic instability is not well identified. We report a case of a young man, previously healthy, presenting with fever, hypotension requiring vasopressors and pancytopenia. Extensive workup was unrevealing for possible infective, inflammatory or endocrine causes except for vitamin B12 deficiency. Fever and haematological parameters stabilised after adequate supplementation of cyanocobalamin (vitamin B12 ).